RELACIONES INTRAFAMILIARES Y SU INFLUENCIA EN EL RENDIMIENTO ACADÉMICO DE LAS Y LOS ESTUDIANTES Y LA INTERVENCIÓN DEL TRABAJADOR SOCIAL - Masa Sarango, Génesis Lizbeth (2019)
The present research work is based on a study made to the students, teachers and parents of the Educational Unit "Pío Jaramillo Alvarado" evening section of the Tenth Year of Basic General Education parallel "A" of the city of Loja, in order to determine the influence of intrafamilial relationships on the academic performance of students and thus propose a Social Action Plan to strengthen the bond of trust between parents and children, through talks, workshops and finally with recreational activities where union, communication, harmony and, above all, achieve the integral well-being of all those involved. In the same sense for the development of the investigative work several materials, methods and techniques were used that contributed with the severity and pertinence for the collection of information, same that were applied to the educational triad. The main findings obtained in the investigation show that the problems caused within the home such as: lack of communication, affection, distrust, parents' disinterest towards their children during their educational training stage, which directly affect their academic studies. On the other hand, the results of the research indicate that the low academic performance is also due to the abandonment by the father figure, teenage pregnancy, use of illicit substances, for work reasons and irresponsibility on the part of the students. The intervention of the social worker in this problem is in charge of favoring the establishment and strengthening of the relationships between the school environment, the family and the community before all those obstacles that impede the integral development of the student. Its function is to promote, guide and contribute to a comprehensive education, responding to those factors that affect the harmonious development of the teaching-learning process. The intervention activities are focused on the student, family and educational institution to improve the situation experienced. Therefore, as an alternative solution and contribution to the research, a social action plan was designed focused on strengthening the bonds of trust between parents and children